The association between the interval from biopsy to radical prostatectomy and biochemical recurrence in patients with intermediate- and high-risk prostate cancer - Siech, Carolin; Wenzel, Mike; Knoblich, Georgina; Cano Garcia, Cristina; Humke, Clara; Preisser, Felix; Traumann, Miriam; Kluth, Luis A.; Chun, Felix K. H.; Mandel, Philipp (Frontiers in Oncology, 2025)
ObjectiveTo investigate the association between the interval from biopsy to radical prostatectomy (RP) and biochemical recurrence (BCR) in prostate cancer patients.MethodsWithin a tertiary-care database (01/2014 to 06/2023), D’Amico intermediate- and high-risk prostate cancer patients were stratified according to interval from biopsy to RP (≤3 vs. >3-≤6 months). Kaplan-Meier survival analyses and Cox regression models addressed BCR.ResultsOf 680 patients, 328 vs. 153 exhibited intermediate-risk prostate cancer and had interval from biopsy to RP ≤3 vs. >3-≤6 months. Similarly, 158 vs. 41 exhibited high-risk prostate cancer and had interval from biopsy to RP ≤3 vs. >3-≤6 months. Median interval from biopsy to RP was 59 vs. 113 days in intermediate- and 55 vs. 117 days in high-risk patients, respectively. In both intermediate- and high-risk patients, rates of adverse histopathological outcomes, namely pT3/pT4, pN1, and R1 status, did not differ according to interval from biopsy to RP. In survival analyses, three-year BCR-free survival rates were 82 vs. 88% in intermediate-risk (p=0.5) and 76 vs. 75% in high-risk patients (p=1). In multivariable Cox regression models, BCR did not significantly differ according to interval from biopsy to RP in intermediate- (hazard ratio 0.85, 95% confidence interval 0.49-1.46; p=0.5) and high-risk patients (hazard ratio 1.05, 95% confidence interval 0.50-2.22; p=0.9).ConclusionsBoth intermediate- and high-risk prostate cancer patients with an interval from biopsy to RP >3-≤6 months did not differ from those treated with RP ≤3 months after biopsy, regarding adverse histopathological outcomes and BCR rates. Therefore, it might be safe to postpone RP up to six months.